Micrometry of different category oocytes recovered from goat ovaries - KUMAR, NAVNEET; PARAMASIVAN, S; SOOD, PANKAJ; SINGH, MADHUMEET (The Indian Journal of Animal Sciences, 2014)
The ovaries from goats (20), 1-4 year old were collected from loeul abattoir. The oocytes (558) thus recovered by aspiration of visible follicles followed by slicing of the same ovaries were categorized and sUbjected to micrometry under binocular compound microscope using ocular micrometer calibrated with stage micrometer. The average diatneter of categories 1,2,3 and 4 oocytes, with zona pdlucida was 172.59± 0.94 µm, 164.00 ± 0.78 µm, 157.08 ± 1.22 µm and 149.66 ± 1.31 µm respectively. The category 4 oocytcs :covered from aspiration (157.97 j; 1.35 flm) showed statistically signitlcant increase in diameter compared to oocytcs revovered from slicing (147.01 ± 1.58 µm). The average diameter of good quality ooeytes (categories 1,2) recovered from ovaries without corpora lutea was more as compared to the ovaries with corpora luten. Based on the micromctric dimensions it was concluded that good quality oocytes 0, 2) were larger in size as compared to poor quality categories (3, 4) and can be effectively used for in vitro fertilization.